Bridging the Theory-Practice Gap: A Qualitative Portfolio Analysis of Consultancy-as-Pedagogy in Brand Management Education - Yoanita Alexandra; Boby Arinto; Rajesh Prettypal Singh (Ilomata International Journal of Management, 2026)
In contemporary business education, a persistent "theory-practice gap" remains a critical challenge, particularly within marketing and brand management curricula where traditional instruction heavily relies on passive case studies of multinational corporations. To address this gap, this study evaluates the "Consultancy-as-Pedagogy" model, an experiential learning intervention where undergraduate students act as strategic brand consultants for real-world MSMEs. Within the authors’ institution, this gap was historically observed as an operational curriculum challenge. Adopting a Scholarship of Teaching and Learning (SoTL) framework integrated with Kolb's Experiential Learning Cycle, this qualitative action research design systematically analysed 10 comprehensive, student-led strategic branding portfolios representing the collaborative work of 70 students across 10 distinct MSME cases in the Food & Beverage and Beauty sectors. Data were evaluated using Reflexive Thematic Analysis (RTA). The evaluation of the study focuses on student learning outcomes and student reflections on their engagement with MSME. The findings indicate that the model successfully yields immediate, mutually beneficial outcomes. Students demonstrated clear growth in professional readiness, shifting from passive learners to strategic problem-solvers, while MSME owners obtained highly localized, low-to-zero-budget branding assets explicitly tailored to their operational constraints. This research provides a grounded, realistic, and scalable framework for universities seeking to align academic learning with practical, community-based business development.